Report on milestones for care and support under the U.S. National Plan to Address Alzheimer's Disease. Issue 3 (8th February 2016) - ,; Borson, Soo; Boustani, Malaz A.; Buckwalter, Kathleen C.; Burgio, Louis D.; Chodosh, Joshua; Fortinsky, Richard H.; Gifford, David R.; Gwyther, Lisa P.; Koren, Mary Jane; Lynn, Joanne; Phillips, Cheryl; et al.
Abstract: Introduction: Under the U.S. national Alzheimer's plan, the National Institutes of Health identified milestones required to meet the plan's biomedical research goal (Goal 1). However, similar milestones have not been created for the goals on care (Goal 2) and support (Goal 3). Methods: The Alzheimer's Association convened a workgroup with expertise in clinical care, long‐term services and supports, dementia care and support research, and public policy. The workgroup reviewed the literature on Alzheimer's care and support; reviewed how other countries are addressing the issue; and identified public policies needed over the next 10 years to achieve a more ideal care and support system. Results: The workgroup developed and recommended 73 milestones for Goal 2 and 56 milestones for Goal 3. Discussion: To advance the implementation of the U.S. national Alzheimer's plan, the U.S. government should adopt these recommended milestones, or develop similar milestones, to be incorporated into the national plan.